A prática pedagógica na educação a distância transformando a docência: uma análise sobre saberes e desenvolvimento profissional de tutores virtuais - Chaquime, Luciane Penteado (2014)
The flow of information and quick and easy access that you have to them due to the spread of digital information and communication technologies (DICT) is a hallmark of contemporaneity. This scenario originated from the productive and organizational restructuring from capitalism and soon expanded to other social spheres, including education. The insertion of DICT in educational processes enhances the Distance Education (DE) as a way of teaching and learning and redefines the roles of both learner and the teachers. New knowledge and techniques are required from this professional to act as mediator and motivator of educational relationships established in this modality. Such knowledge and expertise, in most cases, are not constructed during initial training and, thus, teaching the way from the experiences they experience in their daily lives. Then, it is understood that the virtual teacher, through their teaching, while that formed and enhances professionally, maturing as a teacher, can also transform their practice in relation to classroom education. Therefore, this study aimed to examine the changes that occur in teaching from the everyday pedagogical practice in distance education, having as subject the teachers who work in virtual courses in Management, Computer for Internet and Profuncionário offered by the Federal Institute of Education, Science and Technology of São Paulo (FISP) through e-Tec Network Brazil. To do so, four specific objectives were elaborated, namely: to identify and analyze possible discrepancies between the prescribed profile and the established profile of virtual teachers of e-Tec Network Brazil/FISP; to map the knowledge built by the teachers throughout the educational experience in DE, identifying their nature; to analyze the perception of teachers in relation to virtual transformations that their practice has suffered through the experience in distance education; to identify and list the key elements that during their practice in distance education, contribute to the maturation/redefinition of the concept of virtual teaching from e-Tec Network Brazil/FISP. Given the research objectives, we used methodological triangulation, in other words, have combined procedures and quantitative and qualitative analysis throughout the investigation. The analyzes show that the pedagogical practice in distance education transforms teaching, because the teachers has the opportunity to review the knowledge basis required for their profession, including expanding it with the construction of new knowledge; through this construction, the teachers have the opportunity to reflect on their role in society, maturing/redefining their identity and conception about the profession; it can constitute an opportunity for professional development for the teachers when understood as a re-professionalization of teaching.